A 0.6 V, low‐power and high‐gain ultra‐wideband low‐noise amplifier with forward‐body‐bias technique for low‐voltage operations. Issue 8 (1st June 2015) - Pandey, Sunil; Singh, Jawar
Abstract : A two‐stage common‐source (CS) low‐noise amplifier (LNA) that uses a forward‐body‐bias technique in N‐type metal–oxide semiconductor devices and intended to achieve a high gain and low power consumption is proposed in this study for ultra‐wideband (UWB) applications. Its first stage yields an exceptionally high gain because of high transconductance ( g m 1 = 16 mS) of the input device. It also shows simultaneous wideband input matching and low‐noise figure (NF) characteristics with the aid of source degenerated inductors. A simple source degenerated CS topology with the shunt‐peaking inductor L d2 is designed as the second stage to enhance the gain response at high frequencies. Using a standard 90 nm complementary metal–oxide semiconductor process, the proposed UWB LNA achieves a gain S 21 ≥ 20 dB in the frequency range of 3.1–10.6 GHz, while consuming only 12.6 mW power from a 0.6 V supply voltage. The simulation results show a minimum NF (NFmin ) below 1.7 dB in the frequency range of 3.1–10.6 GHz and input return loss S 11 < −10 dB in the frequency range of 3.5–10 GHz. When a two tone test is performed with a frequency spacing of 2 MHz, a high value of third‐order input intercept point of −8 dBm is also achieved.